A Rare Case of Metastatic Desmoplastic Small Round Cell Tumour: Diagnosis and Management - Shahzaib Nabi; Abhijit Saste; Rohit Gulati (Case Reports in Oncological Medicine)
A 26-year-old male without any significant past medical history presented to the hospital with shortness of breath, cough, pleuritic chest pain, and weight loss for the past 3 months. On chest CT, he was found to have extensive mediastinal and hilar lymphadenopathy and multiple pulmonary nodules. On physical examination, a right groin mass was noted which had been slowly growing for the past 2 years. Ultrasound of the groin showed complex solid mass with internal vascular channels. CT guided biopsy of the mass showed desmoplastic small round cell tumour. His hospital course was complicated by hypoxic respiratory failure requiring emergent intubation and ICU admission where he completed one cycle of vincristine, cyclophosphamide, and doxorubicin with subsequent improvement, followed by extubation. His condition continued to improve after second cycle of chemotherapy and he was ultimately discharged in a stable condition to continue outpatient chemotherapy after a 2-month inpatient stay.